Effectiveness of Village-Owned Enterprises (BUMDesa) adaptation in the Covid-19 Pandemic era in Bulukumba Regency - Sosiawan, Aryo; Latief, Muh. Iqbal; Muhammad, Rahmat (Sangia Research Media and Publishing, 2023)
This research aims to explain the effectiveness of Adaptation of Village-Owned Enterprises (BUMDesa) in the Covid-19 Pandemic era in Bulukumba Regency. This research uses qualitative research methods. The results showed that during the Covid-19 Pandemic in carrying out social adaptation to the community was driven by three main actors played by the Regency Government, Village Government and Village-Owned Enterprises Management. the three main actors collaborate with each other to create prosperity for the Village community through Village-Owned Enterprises by means of the Regency Government as a Policy Maker for the Implementation of Health Protocols, which then the Village Government and the elements in it together with the Village-Owned Enterprises Management follow up on decisions from the Regency Government which are adjusted in the form of each rule in each Business Unit decided at the Village Consultative Meeting. Aspects that influence during the Covid-19 Pandemic related to adaptation carried out by the Village-Owned Enterprises Management from the Social aspect, namely the provision of assistance to the community which is limited due to decreased revenue at the Village-Owned Enterprises. Then from the Economic aspect, namely the decline in revenue of the Village-Owned Enterprises during the Covid-19 Pandemic and from the Health aspect, namely the implementation of public health protocols that have not fully run to the maximum.